Ohwia caudata aqueous extract attenuates senescence in aging adipose-derived mesenchymal stem cells - Tsung-Jung Ho; Bruce Chi-Kang Tsai; Goswami Debakshee; Marthandam Asokan Shibu; Chia-Hua Kuo; Chih-Hsueh Lin; Pi-Yu Lin; Shinn-Zong Lin; Wei-Wen Kuo; Chih-Yang Huang (Heliyon, 2024)
Stem cells exhibit pluripotency and self-renewal abilities. Adipose-derived mesenchymal stem cells can potentially be used to reconstruct various tissues. They possess significant versatility and alleviate various aging-related diseases. Unfortunately, aging leads to senescence, apoptosis, and a decline in regenerative capacity in adipose-derived mesenchymal stem cells. These changes necessitate a strategy to mitigate the effects of aging on stem cells. Ohwia caudata (O. caudata) has therapeutic effects against several illnesses. However, studies on whether O. caudata has therapeutic effects against aging are lacking. In this study, we aimed to identify potential therapeutic anti-aging effects in the crude aqueous extract of O. caudata on adipose-derived mesenchymal stem cells. Using 0.1 μM doxorubicin, we induced aging in human adipose-derived mesenchymal stem cells (hADMSCs) and evaluated whether various concentrations of O. caudata aqueous extract exhibit anti-aging effects on them. The O. caudata extract exhibited significant antioxidant effects on hADMSCs without any toxicity. Furthermore, after treatment with the O. caudata aqueous extract, the levels of mitochondrial superoxide, DNA double-strand breaks, and telomere shortening were reduced in the hADMSCs subjected to doxorubicin-induced aging. The extract also suppressed doxorubicin-induced aging by upregulating klotho and downregulating p21 in hADMSCs. These ﬁndings indicated that the O. caudata extract exhibited anti-aging properties that modulated hADMSC homeostasis. Therefore, it could be a potential candidate for restoring the self-renewal ability and multipotency of aging hADMSCs.